ANALISIS DAMPAK GAME ONLINE TERHADAP PERILAKU SOSIAL PESERTA DIDIK KELAS VI SD NEGERI LIMBANGAN 02 - Berliana Ayu Puspita; Farhan Saefudin Wahid; Toharudin, Moh (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2025)
This study aims to examine the impact of online games on the social behavior of sixth-grade students at SD Negeri Limbangan 02. The research employed a qualitative descriptive method. Primary data consisted of interview transcripts and observation notes, obtained from 34 informants who were selected as samples in the study. Secondary data were collected through participatory observation at SD Negeri Limbangan 02. To ensure data validity, the study used source and technique triangulation. The data analysis technique in qualitative research includes four stages: data collection, data reduction, data presentation, and conclusion drawing. Based on the findings, it can be concluded that online games have both positive and negative effects on students’ social behavior. On the positive side, online games can enhance concentration, foster teamwork, improve communication skills, and develop empathy and respect for peers. Social interaction through gaming may also broaden students’ social networks. However, excessive use of online games has negative impacts, including reduced face-to-face interaction, increased aggressive behaviors such as irritability and the use of inappropriate language, declining politeness toward teachers and peers, decreased motivation to learn, and emotional as well as financial dependence on online gaming.